Quantum computation and quantum information - Nielsen, Michael A.; Chuang, Isaac L. (New Delhi: Cambridge University Press, 2002)
One of the most cited books in physics of all time, Quantum Computation and Quantum Information remains the best textbook in this exciting field of science. This 10th anniversary edition includes an introduction from the authors setting the work in context. This comprehensive textbook describes such remarkable effects as fast quantum algorithms, quantum teleportation, quantum cryptography and quantum error-correction. Quantum mechanics and computer science are introduced before moving on to describe what a quantum computer is, how it can be used to solve problems faster than 'classical' computers and its real-world implementation. It concludes with an in-depth treatment of quantum information. Containing a wealth of figures and exercises, this well-known textbook is ideal for courses on the subject, and will interest beginning graduate students and researchers in physics, computer science, mathematics, and electrical engineering.
Introduction and Overview -- Introduction to Quantum Mechanics -- Introduction to Computer Science -- Quantum Computation -- The Quantum Fourier Transform and its Applications -- Quantum Search Algorithms -- Quantum Computers : Physical Realization -- Quantum Noise and Quantum Operations -- Distance Measures for Quantum Information -- Quantum Error-Correction -- Entropy and Information -- Quantum Information Theory
Includes bibliography and index
Keywords: Physics; Quantum Theory